Perilaku Coping Masyarakat Menghadapi Banjir - Mohammad Khasan; Mochamad Widjanarko (Jurnal Psikologi: PITUTUR, 2011)
Various disasters hit Indonesia causing death, injury, permanent handicap, psychological trauma, and even harvest failure. Setrokalangan Village of Kudus Regency is frequently flooded caused by the overflowing of Wulan River. The community is forced to have a coping behaviour in dealing with the flood in order to survive. The purpose of the research is to know the type and intensity of the coping behaviour of Setrokalangan community who are victims of flood. Not all individu of the community from Setrokalangan Village can be the informant. Only those who have the specific identification which meets with research main problem can be the informants. The identifications are indigenous villagers of Setrokalangan Village, Kaliwungu Sub-district, Kudus Regency and victims of flood. Coping behaviour in the research refers to Lazarus and Folkman definition. Coping strategy is divided into two, problem focused coping (PFC) and emotional focused coping (EFC), which consist of 8 forms of coping strategy.They are confrontation, social support, problem solving plan, self control, diversion, positive value, responsibility to be taken, running or avoiding. Based on the coding of the interview and observation with three research informants, it can be concluded that the coping behaviour of the community of Setrokalangan Village of Kudus Regency who are the victims of flood tends to be confrontation, problem solving plan, self control, and running or avoiding.